IMPLEMENTATION AND EVALUATION OF INTERACTIVE EDUCATIONAL GAME OF WADAI BANJAR AS AN EFFORT TO PRESERVE TRADITIONAL CAKES OF SOUTHERN KALIMANTAN - Aulia Akhrian Syahidi; Rizky Pamuji; Nuruddin Wiranda (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
When tourists visit an area, they will definitely look for food and cakes typical of the area to taste or as souvenirs. Including when tourists visit South Kalimantan, tourists will also look for special cakes often called Wadai Banjar, there are various types of Wadai Banjar and must be preserved. Among the younger generation now, Wadai Banjar must also be introduced and strived to be preserved. Based on the information, the purpose of this research is to design, developing, and evaluating the Wadai Banjar educational game. The method used is the Game Development Life Cycle (GDLC) which consists of initiation, pre-production, production, testing, beta, and release, followed by an evaluation of the use of the game application. A total of 100 users have been involved in evaluating the use of the application. The result of this study is that the educational game that has been designed and built can function according to the test features provided and can be released to users. The evaluation of use provides results that the Wadai Banjar educational game application can provide fun, comfort, a fitting and attractive user interface, can find out and learn in recognizing the types of Wadai Banjar, useful and as an effort to introduce and preserve traditional cakes typical of South Kalimantan. Then as many as 70 users are more interested if this Wadai Banjar educational game is desktop-based, because interaction is more flexible and a mouse is needed as the main input media in performing actions.